Nearest-neighbor amino acids of specificity-determining residues influence the activity of engineered Cre-type recombinases - Anjali Soni (Nature Portfolio, 2020)
Abstract The tyrosine-type site-specific DNA recombinase Cre recombines its target site, loxP, with high activity and specificity without cross-recombining the target sites of highly related recombinases. Understanding how Cre achieves this precision is key to be able to rationally engineer site-specific recombinases (SSRs) for genome editing applications. Previous work has revealed key residues for target site selectivity in the Cre/loxP and the related Dre/rox recombinase systems. However, enzymes in which these residues were changed to the respective counterpart only showed weak activity on the foreign target site. Here, we use molecular modeling and dynamics simulation techniques to comprehensively explore the mechanisms by which these residues determine target recognition in the context of their flanking regions in the protein–DNA interface, and we establish a structure-based rationale for the design of improved recombination activities. Our theoretical models reveal that nearest-neighbors to the specificity-determining residues are important players for enhancing SSR activity on the foreign target site. Based on the established rationale, we design new Cre variants with improved rox recombination activities, which we validate experimentally. Our work provides new insights into the target recognition mechanisms of Cre-like recombinases and represents an important step towards the rational design of SSRs for applied genome engineering.